Using Social Media Platforms By English For Specific Purposes Students At The National Institute Of Technology - Zanyar Nathir Ghafar; Akam Azad Mohamedamin; Ikhsan Nendi (Journal Of Social Science (JoSS), 2023)
This research analyses how students enrolled in the English for Specific Purposes program at the National Institute of Technology utilize various social media platforms during their English studies. The students are studying English at the National Institute of Technology. The researcher collected the data via a questionnaire filled out by 50 students and through semi-structured interviews with 10 male and female students. The results of the qualitative interviews were studied via the lens of an experienced case study and coded according to themes, while the quantitative questionnaire results were reviewed through the lens of fundamental statistics. According to the study, social platforms are crucial for students learning English as a foreign language. Currently, students use seven different social platforms to learn English, enhance their language skills, and support in developing their language competency. On the other hand, students at the National Institute of Technology taking English lessons for various reasons utilize Instagram more than other social media sites to practice their English at home and in other academic settings.